Wangari's trees of peace : a true story from Africa - Winter, Jeanette (Harcourt, 2008)
This true story of Wangari Maathai, environmentalist and winner of the Nobel Peace Prize, is a shining example of how one woman's passion, vision, and determination inspired great change.